A study of the role of glucose transporter 1 (Glut1) in white spot syndrome virus (WSSV) infection. Issue 2 (October 2015) - Huang, Huai-Ting; Chan, Hoi-Ling; Shih, Tsai-Yen; Chen, Li-Li
Abstract White spot syndrome virus (WSSV) is a large enveloped DNA virus, and it causes a serious disease that has led to severe mortalities of cultured shrimps in many countries. To determine the mechanism of virus entry into the cell and to establish an antiviral strategy, the cell receptor for virus entry and receptor binding protein should be identified. A shrimp cell surface protein, glucose transporter1 (Glut1), was found to interact with WSSV in previous study. In this study, this Glut1 was confirmed to have the ability of transporting glucose, and this gene can also be found in other shrimp species. The interaction between Glut1 and some other WSSV envelope proteins in the infectome structure was verified by far western blot and His pull down assay. In vitro and in vivo neutralization using recombinant partial Glut1 revealed that the large extracellular portion of Glut1 could delay WSSV infection. Also, shrimps which were knocked-down Glut1 gene by treated with dsRNA before WSSV challenge showed decreased mortality. These results indeed provide a direction to develop efficient antiviral strategies or therapeutic methods by using Glut1.